Predictive Technologies: Can Smart Tools Augment the Brain's Predictive Abilities? - Pezzulo, Giovanni; D'Ausilio, Alessandro; Gaggioli, Andrea (Frontiers in Neuroscience, 2016)
The ability of “looking into the future” – namely, the capacity of anticipating future states of the environment or of the body – represents a fundamental function of human (and animal) brains. A goalkeeper who tries to guess the ball’s direction; a chess player who attempts to anticipate the opponent’s next move; or a man-in-love who tries to calculate what are the chances of her saying yes – in all these cases, people are simulating possible future states of the world, in order to maximize the success of their decisions or actions. Research in neuroscience is showing that our ability to predict the behaviour of physical or social phenomena is largely dependent on the brain’s ability to integrate current and past information to generate (probabilistic) simulations of the future. But could predictive processing be augmented using advanced technologies? In this contribution, we discuss how computational technologies may be used to support, facilitate or enhance the prediction of future events, by considering exemplificative scenarios across different domains, from simpler sensorimotor decisions to more complex cognitive tasks. We also examine the key scientific and technical challenges that must be faced to turn this vision into reality.